PENENTUAN STATUS MUTU AIR SUNGAI SERAYU MENGGUNAKAN TEKNOLOGI ONLINE MONITORING (ONLIMO) DENGAN METODE ANALISA STORET - Arinda, Evitta Sherin; Wahyono, Heru Dwi; Santoso, Arif Dwi (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2023)
Serayu River has decrease in capacity, both in quality and quantity. This condition causes the function and performance of the river as a source of water for community activities to be less than optimal. Efforts to improve monitoring of the Serayu River water quality require a continuous monitoring program implemented online. Therefore, a more reliable effort to control water pollution is needed in order to maintain water quality according to its purpose. The purpose of the research is to periodically monitor water quality and determine the status of water quality in the Serayu River. It is hoped that this explanation will be used as a comparison for manual monitoring activities that have been did in the Serayu River previously and as a reference for monitoring water quality in other locations. The method of measuring water quality is using online monitoring system and determining the status of water quality using the Storet analysis method. Samples were taken and measured from 2 stations namely Bendung Wanganaji and Bendung Gerak Serayu using mulptiprobe sensors consisting of parameters of temperature, DO, pH, TDS, conductivity, turbidity, nitrate and ammonia. Data from sensor measurements are sent and analyzed online by the onlimo system. The data that has been analyzed are then verified and reanalyzed using the Storet method. The results of the analysis of water quality monitoring of Serayu River state that the quality in Serayu River water is classified as light to moderate polluted. ABSTRAK Sungai Serayu telah mengalami penurunan kapasitas, baik secara kualitas maupun kuantitas. Kondisi ini menyebabkan fungsi dan kinerja sungai sebagai sumber air bagi aktivitas masyarakat menjadi kurang optimal. Upaya meningkatkan pemantauan kualitas air Sungai Serayu memerlukan program pemantauan yang kontinyu dan dilaksanakan secara online. Oleh karena itu diperlukan upaya pengendalian pencemaran air yang lebih handal dalam rangka untuk menjaga kualitas air sesuai dengan peruntukannya. Tujuan penelitian yaitu untuk memantau kualitas air secara berkala dan menentukan status mutu air di Sungai Serayu. Paparan ini diharapkan menjadi bahan komparasi kegiatan pemantauan manual yang telah dilakukan di Sungai Serayu sebelumnya dan menjadi acuan pemantauan kualitas air di lokasi lain. Metode pengukuran kualitas air menggunakan sistem online monitoring dan penentuan status mutu air menggunakan metode analisis Storet. Sampel diperoleh dari 2 stasiun yaitu Bendung Wanganaji dan Bendung Gerak Serayu menggunakan mulptiprobe sensor yang terdiri dari suhu, DO, pH, TDS, DHL, turbiditas, nitrat dan amonia. Data hasil pengukuran sensor dikirim dan dianalisis secara online oleh sistem onlimo. Data hasil analisis selanjutnya diverifikasi dan dianalisis ulang menggunakan metode Storet. Hasil analisis pemantauan kualitas air Sungai serayu menyatakan kualitas air Sungai Serayu tergolong dalam klasifikasi tercemar ringan hingga tercemar sedang. Kata Kunci: Sungai Serayu, status mutu air, Storet, Onlimo, pemantauan online